Career Decision-making Self-Efficacy of Higher Education Students in Tanzania: Does Age, Gender, and Year of Study Matter? - Amani, Jaquiline (Papers in Education and Development, 2016)
This article presents the findings of study that deployed a cross-sectional survey design to examine a perceived self-efficacy in career decision-making of undergraduate students in Tanzania. Specifically, the study examined the extent to which age, gender, and year of study influence self-efficacy in career decision-making among students in higher education institutions of Tanzania. The study used a sample of 204 business and engineering undergraduate students randomly drawn from two purposively selected public higher education institutions the University of Dar es Salaam and the University of Dodoma. The results showed that the majority of respondents had high career decision-making self-efficacy in terms of goal selection, occupational information, problem-solving, planning, and self-appraisal. Moreover, with the exception of age, the t-test results revealed significant differences in career self-efficacy between female and male students as well as between first and final year students. The results contribute to a better understanding of the development of career decision-making self-efficacy in relation to the students ' gender, age, and year of study in sub-Saharan Africa. Key words: Perceived career self-efficacy, university students, age, gender, year of study, Tanzania